Excudebat Leonhardus Formica: Leonhard Formica (Lenart Mravlja) und seine Musikdrucke - Marko Motnik (Muzikološki Zbornik, 2015)
Lenart Mravlja, also named Leonhard Formica, is one of the numerous personalities from Carniola who worked abroad in the sixteenth century. After being educated in Ljubljana and in several protestant German towns, Formica moved to Vienna at the end of the 1580s where he founded a printing office. Before his death in 1605, he produced approximately 70 books, among which are five high quality music prints.